(untitled) (Journal of Accessibility and Design for All, 2015)
Many people with disabilities face considerable barriers while shopping in grocery stores. One such barrier is that they cannot find their way around easily, especially when they visit the grocery store for the first time and have not yet built a cognitive map in their memory. They may also experience delays in finding the right product or waiting for assistance from store employees, thus leading them to rely on family, friends, relatives, or volunteers to help them with their shopping. Problems start when these people are not available, in which case the individual is forced to cancel their visit to the grocery store and reschedule the trip. Grocery stores include many different zones and services, the aisles area being one of the main barriers to access for people with different disabilities. This area features many different sections such as canned goods, dry packaged goods, spices, drinks and snacks, baking supplies, baby items, cereals, cleaning products, pet supplies, and health and beauty items. For visually impaired individuals, however, it can be hard to reach these various sections and find the relevant products. The objective of this research is to design an inclusive and innovative wayfinding system in grocery stores for visually impaired shoppers in order to help them find the center zone, orient between different aisles, decide where to go, move easily between different sections, and select products with ease. The research approach will be based on the literature review and the application of the Delphi method.